Rheumatoid arthritis and bacterial infections - N L Prokopjeva; N N Vesikova; I M Marusenko; V A Ryabkov (Научно-практическая ревматология)
To study features of bacterial infections course in pts with rheumatoid arthritis (RA) and changes of laboratory measures after focus of infection sanation. Material and methods. 46 pts with definite rheumatoid arthritis were examined at the time of comorbid infection (Cl) detection and after infection focus sanation. Bacteriological test with evaluation of flora sensitivity to antibiotics by disco-diffusion method was performed at baseline and after the course of antibacterial therapy to assess its efficacy. Hemogram, serum fibrinogen, rheumatoid factor, circulating immune complexes (CIC), C-reactive protein levels were assessed. Serum interleukin (IL) 1(3, IL6 and neopterin concentrations were examined by immune-enzyme assay in a part of pts. Typical clinical features of Cl were present in only 28 (60,9%) pts. 13 (28,3%) pts had fever, 12 (26,0%) — leukocytosis, 15 (32,6%) — changes of leucocyte populations. Some laboratory measures (thrombocytes, fibrinogen, CIC, neopterin levels) significantly decreased (p<0,05) after infection focus sanation without correction of disease modifying therapy. Cl quite often develop as asymptomatic processes most often in pts with high activity and can induce disturbances promoting appearance of endothelial dysfunction, atherothrombosis and reduction of life duration. So timely detection and proper sanation of infection focuses should be performed in pts with RA